Sugaring as a deviant career: Modes of entering sugar relationships and social stigmas. Issue 4 (3rd April 2023) - Scull, Maren T.
ABSTRACT: While the research on sugaring has expanded in recent years, there are still many gaps in our understanding of these relationships and how women begin them. Therefore, in this paper I draw from 48 in-depth interviews to understand the methods by which women enter into sugar arrangements and the extent to which this process is intentional, inadvertent, or coerced. Specifically, I draw from the literature on deviant careers to discuss three modes of entry which include drifting, entering via conscious decision, and entering defensively. Additionally, I focus on the public and enacted stigmas women experience once they enter the sugar lifestyle. Specifically, these stigmas came in the form of others conflating sugaring with prostitution, receiving negative reactions due to the age disparity between sugar partners, being labeled immoral, and being called a "greedy gold digger."